2014
DOI: 10.3109/14397595.2014.931908
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics of IgG4-related retroperitoneal fibrosis among patients initially diagnosed as having idiopathic retroperitoneal fibrosis

Abstract: Objective. The purpose of our study was to determine the number of IgG4-related retroperitoneal fibrosis (RPF) cases that were initially diagnosed as idiopathic RPF and to investigate clinical characteristics of IgG4-related RPF. Methods. We retrospectively reviewed the medical records of 41 RPF patients who were treated at our tertiary care medical center in South Korea between January 2000 and January 2013. We identified cases of 19 patients in which a diagnosis was made based on percutaneous biopsy or surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 21 publications
3
23
2
3
Order By: Relevance
“…As for RPF, Khosroshahi et al demonstrated that IgG4-related RPF was identified in 57% of the total cohort, and that the IgG4-related RPF patients had lymphoplasmacytic infiltrate, storiform fibrosis, or tissue eosinophilia in retroperitoneal biopsies at a significantly higher rate than observed in non-IgG4-related RPF patients (21). Koo et al also compared IgG4-related RPF with non-IgG4-related RPF, and reported the recurrence rate of IgG4-related RPF to be significantly higher than that of non-IgG4-related RPF (22). In this case, some histopathologic features, such as epithelioid granulomas and infiltration of neutrophils around the small vessels, were incompatible with IgG4-RD, possibly suggesting a difference in non-IgG4-related MFS from IgG4-RD.…”
Section: Discussionmentioning
confidence: 73%
“…As for RPF, Khosroshahi et al demonstrated that IgG4-related RPF was identified in 57% of the total cohort, and that the IgG4-related RPF patients had lymphoplasmacytic infiltrate, storiform fibrosis, or tissue eosinophilia in retroperitoneal biopsies at a significantly higher rate than observed in non-IgG4-related RPF patients (21). Koo et al also compared IgG4-related RPF with non-IgG4-related RPF, and reported the recurrence rate of IgG4-related RPF to be significantly higher than that of non-IgG4-related RPF (22). In this case, some histopathologic features, such as epithelioid granulomas and infiltration of neutrophils around the small vessels, were incompatible with IgG4-RD, possibly suggesting a difference in non-IgG4-related MFS from IgG4-RD.…”
Section: Discussionmentioning
confidence: 73%
“…Immunohistochemical and histopathological examinations of retroperitoneal tissue showed lesions specific for IgG4-RD in about half (47–59%) of patients with IRF [2, 3, 32]. …”
Section: Igg4-related Disease and Idiopathic Retroperitoneal Fibrosismentioning
confidence: 99%
“…However, 46–50% of cases of IgG4-related RPF show the involvement of organs located outside the retroperitoneal space; hence it is essential to distinguish these patients [2, 3]. Furthermore, the analysis of Koo et al [32] revealed that a group with IgG4-related RPF had a significantly higher recurrence rate compared to IRF; therefore the authors suggest the need for more aggressive immunosuppressive therapy and longer duration of maintenance treatment.…”
Section: Igg4-related Disease and Idiopathic Retroperitoneal Fibrosismentioning
confidence: 99%
“…12 Celle-ci a été identifiée dans 47-58 % des patients ayant déjà reçu un diagnostic de FPR idiopathique. 13,14 De même, environ 50 % des anévrismes inflammatoires de l'aorte abdominale sont liés aux IgG4. 15 Cependant, nous ne disposons que de peu d'informations sur la pathogenèse de cette maladie et la relation entre les formes de la FRP liée et non liée aux IgG4.…”
Section: Fibrose Rétropéritonéaleunclassified
“…12 La maladie à IgG4 est responsable seulement d'une partie des cas de FRPI (50 %). 13,14 La possibilité d'un terrain prédisposé, voire de facteurs génétiques, a été envisagée. Des études génétiques ont montré une forte association entre FRPI et HLA-DRB1*03, allèle lié à de nombreuses MAI telles que le diabète de type 1, la myasthénie grave et la thyroïdite autoimmune.…”
Section: La Frpi Et La Maladie à Igg4unclassified